в объяснении
Объяснение:
аб-б/б²=аб-1/б=аб²/б-1/б=(аб²-1)/б
4x²-y²/2x-y=(2x-y)(2x+y)/(2x-y)=2x+y
2a-2c+ax-cx/(4-x²)=(2(а-c)+x(a-c))/((2-x)(2+x))=(2+x)(a-c)/((2-x)(2+x))=(a-c)/(2-x)
x²⁰y³⁰+x⁸y⁴⁸/x¹³y+xy²⁰=x⁸y²⁰(x¹²+y²⁸)/(xy(x¹²+y²⁸))=x⁷y¹⁹
(x³-64y³)/(x-4y)=(x-4y)(x²+4xy+16y²)/(x-4y)=x²+4xy+16y²
в объяснении
Объяснение:
аб-б/б²=аб-1/б=аб²/б-1/б=(аб²-1)/б
4x²-y²/2x-y=(2x-y)(2x+y)/(2x-y)=2x+y
2a-2c+ax-cx/(4-x²)=(2(а-c)+x(a-c))/((2-x)(2+x))=(2+x)(a-c)/((2-x)(2+x))=(a-c)/(2-x)
x²⁰y³⁰+x⁸y⁴⁸/x¹³y+xy²⁰=x⁸y²⁰(x¹²+y²⁸)/(xy(x¹²+y²⁸))=x⁷y¹⁹
(x³-64y³)/(x-4y)=(x-4y)(x²+4xy+16y²)/(x-4y)=x²+4xy+16y²